Sequential Growth and Etching of Gold Nanocrystals Revealed by High‐Resolution Liquid Electron Microscopy (Phys. Status Solidi A 7∕2019). Issue 7 (10th April 2019) - Kim, Sang Yun; Dae, Kyun Seong; Koo, Kunmo; Kim, Daewoon; Park, Jungjae; Yuk, Jong Min
Abstract : Gold Nanocrystals Direct observation for growth and etching of colloidal nanocrystals will likely benefit rational design of specific nanoparticles. In this study, the graphene liquid cell electron microscopy not only provides the environment for growth and oxidative etching of colloidal gold nanocrystals, but also proves whole process from growth to etching. Direct observation demonstrates different kinetics at each step. More details can be found in article number1800949 by Sang Yun Kim, Jong Min Yuk, and co‐workers.